Preparation method of defoaming-free thermosetting resin
By using a high boiling point silane coupling agent as a solvent, the complex problem of defoaming steps in preparing thermosetting resins in Grubbs second-generation catalyst was solved, and the effect of no bubbles on the surface of the product was achieved, with simple operation and excellent performance.
Patent Information
- Application Number
- CN202311029838.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-16
- Publication Date
- 2025-02-21
AI Technical Summary
Prior art When preparing thermosetting resins using Grubbs second-generation catalysts, it is necessary to remove the solvent dichloromethane through a vacuum step, resulting in complex operation and potentially leaving bubbles, affecting the aesthetics and mechanical properties of the parts.
A high-boiling point silane coupling agent is used as the solvent for Grubbs second-generation catalyst, which eliminates the defoaming step and is directly subjected to stage heating and curing, and the surface of the obtained product is free of bubbles.
The process route is simplified and the operating efficiency is improved. The obtained resin material parts are smooth and bubble-free, and their aesthetics and mechanical properties are improved.
Smart Images

Figure CN119490627A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a method for preparing a thermosetting resin. Background Art
[0002] Polydicyclopentadiene (PDCPD) is a thermosetting polymer resin material derived from dicyclopentadiene (DCPD) by ring-opening metathesis polymerization (ROMP). It has excellent properties of high flexural modulus, high impact strength, as well as low temperature resistance and corrosion resistance. Compared with epoxy resin, it has the characteristics of lower viscosity and faster reaction speed of the reaction system, and the obtained parts are lighter and have broad application prospects. As an emerging polymer material, PDCPD is widely used in vehicle housings, chemical pipelines, medical equipment and other fields, and the market demand is also increasing.
[0003] Grubbs second-generation catalyst is a commonly used ring-opening metathesis polymerization catalyst. As a single-component ruthenium carbene catalyst, it is more tolerant to water, oxygen and functional groups than two-component tungsten catalysts and has higher catalytic activity.
[0004] Nowadays, in most patents, Grubbs second-generation catalyst mostly uses dichloromethane as a solvent. After adding it into the resin liquid, vacuum is required to remove the dichloromethane. If the dichloromethane is not completely removed, bubbles will form on the surface of the part, affecting the appearance and mechanical properties.
[0005] The present invention unexpectedly discovered that if a high-boiling-point silane coupling agent is used as the solvent for the Grubbs second-generation catalyst, not only can the degassing step be omitted, the operating efficiency is improved, and the obtained sample has a better appearance, but also the process route of the method of the present invention is simple and the reaction process is controllable. Summary of the invention
[0006] To solve the above problems, the purpose of the present invention is to provide a method for preparing a degassing-free thermosetting resin, which is relatively simple to operate, does not require vacuuming after adding a catalyst, and has no bubble formation on the surface of the obtained part.
[0007] The present invention provides a method for preparing a degassing-free thermosetting resin, comprising:
[0008] A1. Fully mix 100 parts by mass of DCPD and 5 to 20 parts by mass of TCPD to prepare a uniform liquid;
[0009] A2, dissolving 0.02-0.06 parts by weight of Grubbs second generation catalyst and 0.07-0.2 parts by weight of retarder in 5-10 ml of high boiling point silane coupling agent, and adding the mixture to the feed solution of step A1;
[0010] A3. Inject the liquid material obtained in step A2 into the mold, heat it up in stages for curing, and demould to obtain the resin material.
[0011] In a preferred embodiment, in step A2, the retarder is selected from one or any combination of triphenylphosphine, tributyl phosphite and tributyl phosphate.
[0012] In a preferred embodiment, the retarder is triphenylphosphine.
[0013] In a preferred embodiment, in step A2, the high boiling point silane coupling agent is selected from at least one of phenyltrimethoxysilane, p-chlorophenyltrimethoxysilane, 3-aminopropyltriethoxysilane, mercaptopropyltrimethoxysilane, benzyltriethoxysilane, triethoxypentylsilane, methylcyclohexyldimethoxysilane and n-hexyltrimethoxysilane.
[0014] In a preferred embodiment, in step A2, the high boiling point silane coupling agent is phenyltrimethoxysilane.
[0015] In a preferred embodiment, in step A2, the molecular structure of the Grubbs second generation catalyst is:
[0016]
[0017] In a preferred embodiment, in step A2, the staged curing conditions are: 0.25 to 1.5 hours at 60° C. and 0.5 to 1.5 hours at 140° C.
[0018] In a preferred embodiment, the staged curing conditions are: 0.25 hours at 60° C. and 1 hour at 140° C.
[0019] The present invention also provides a PDCPD thermosetting resin prepared by a method for preparing a degassing-free thermosetting resin.
[0020] In a preferred embodiment, the tensile strength of the PDCPD thermosetting resin is ≥55 MPa, and the tensile modulus is ≥1890 MPa.
[0021] In a preferred embodiment, the elongation at break of the PDCPD thermosetting resin is ≥ 28%.
[0022] In a preferred embodiment, the PDCPD thermosetting resin has a flexural strength of ≥79 MPa and a flexural modulus of ≥1876 MPa.
[0023] Without violating the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0024] Due to the adoption of the above technical solution, the present invention has the following beneficial effects:
[0025] (1) A high-boiling-point silane coupling agent represented by phenyltrimethoxysilane is used as a solvent for the Grubbs II catalyst, and no vacuum operation is required;
[0026] (2) High-boiling-point silane coupling agents, represented by phenyltrimethoxysilane, will not vaporize at the reaction temperature, and no bubbles will be formed on the surface of the obtained product.
[0027] (3) The method for preparing the degassing-free thermosetting resin of the present invention has a relatively simple process route and a controllable reaction process.
[0028] BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a surface photo of the resin material part prepared in Comparative Example 1;
[0030] Figure 2 This is a surface photo of the resin material part prepared in Example 2; DETAILED DESCRIPTION
[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meanings as commonly understood by those of ordinary skill in the art to which the invention belongs. Although any methods and materials similar or equivalent to those described herein can be used to implement or test the present invention, preferred methods and materials are described herein. For purposes of the present invention, the following terms are defined below.
[0032] As used herein, the term "about" refers to an amount, level, value, dimension, size, or amount that differs by up to 30%, 20%, or 10% compared to the amount, level, value, dimension, size, or amount of a reference product. Percentages used herein, unless otherwise indicated, are by weight.
[0033] Throughout the specification and claims, unless otherwise required, the following words "comprise" and variations "comprising" and "including" will be understood to imply the inclusion of a stated integer or step, or a group of integers or steps, but not the exclusion of any other integer or step, or other group of integers or steps.
[0034] Experimental Materials:
[0035] name Specification factory Dicyclopentadiene (DCPD) 96% Aladdin Tricyclopentadiene (TCPD) 20% self made Grubbs second generation catalyst 99.95% Aladdin Triphenylphosphine 99% Aladdin Phenyltrimethoxysilane 95% Aladdin
[0036] The present invention is described in detail below in conjunction with specific embodiments. It should be noted that the following embodiments are only used to illustrate the invention, but do not limit the scope of the present invention in any form. In addition, it should be noted that those skilled in the art can make various modifications and improvements to the present invention. These all belong to the protection scope of the present invention.
[0037] Embodiment 1:
[0038] The DCPD raw material was heated to 150-170°C and kept at a constant temperature for 6 hours. The feed liquid was cooled to room temperature and light components were removed by vacuum to obtain TCPD with a DCPD content of 20%. The TCPD described in the present application is the mixed solution prepared in this example.
[0039] Embodiment 2:
[0040] 100 parts by mass of DCPD and 5 parts by mass of TCPD of Example 1 were fully mixed to prepare a uniform resin liquid. 0.06 parts by mass of Grubbs second-generation catalyst and 0.2 parts by mass of triphenylphosphine were dissolved in 5 ml of phenyltrimethoxysilane and added to the resin liquid. The resin liquid was injected into the mold, heated to 60°C, kept at a constant temperature for 1 hour, and then heated to 140°C again, kept at a constant temperature for 1 hour for staged temperature curing, then cooled and demolded to obtain a resin material.
[0041] Embodiment 3:
[0042] 100 parts by mass of DCPD and 5 parts by mass of TCPD of Example 1 were fully mixed to prepare a uniform resin liquid. 0.03 parts by mass of Grubbs second-generation catalyst and 0.1 parts by mass of triphenylphosphine were dissolved in 5 ml of phenyltrimethoxysilane and added to the resin liquid. The resin liquid was injected into the mold, heated to 60°C, kept at a constant temperature for 1 hour, and then heated to 140°C again, kept at a constant temperature for 1 hour for staged temperature curing, then cooled and demolded to obtain the resin material.
[0043] Embodiment 4:
[0044] 100 parts by mass of DCPD and 5 parts by mass of TCPD of Example 1 were fully mixed to prepare a uniform resin liquid. 0.02 parts by mass of Grubbs second-generation catalyst and 0.07 parts by mass of triphenylphosphine were dissolved in 5 ml of phenyltrimethoxysilane and added to the resin liquid. The resin liquid was injected into the mold, heated to 60°C, kept at a constant temperature for 1 hour, and then heated to 140°C again, kept at a constant temperature for 1 hour for staged temperature curing, then cooled and demolded to obtain a resin material.
[0045] Embodiment 5:
[0046] 100 parts by mass of DCPD and 10 parts by mass of TCPD of Example 1 were fully mixed to prepare a uniform resin liquid. 0.06 parts by mass of Grubbs second-generation catalyst and 0.2 parts by mass of triphenylphosphine were dissolved in 5 ml of phenyltrimethoxysilane and added to the resin liquid. The resin liquid was injected into the mold, heated to 60°C, kept at a constant temperature for 1 hour, and then heated to 140°C again, kept at a constant temperature for 1 hour for staged temperature curing, then cooled and demolded to obtain a resin material.
[0047] Embodiment 6:
[0048] 100 parts by mass of DCPD and 20 parts by mass of TCPD of Example 1 were fully mixed to prepare a uniform resin liquid. 0.03 parts by mass of Grubbs second-generation catalyst and 0.1 parts by mass of triphenylphosphine were dissolved in 5 ml of phenyltrimethoxysilane and added to the resin liquid. The resin liquid was injected into the mold, heated to 60°C, kept at a constant temperature for 1 hour, and then heated to 140°C again, kept at a constant temperature for 1 hour for staged temperature curing, then cooled and demolded to obtain a resin material.
[0049] Comparative Example 1:
[0050] 100 parts by mass of DCPD and 5 parts by mass of TCPD of Example 1 were fully mixed to prepare a uniform resin liquid. 0.06 parts by mass of Grubbs second-generation catalyst and 0.2 parts by mass of triphenylphosphine were dissolved in 1 ml of dichloromethane, added to the resin liquid, and the dichloromethane solvent was removed by vacuum until no bubbles emerged. The resin liquid was injected into the mold, heated to 60°C, kept at a constant temperature for 1 hour, and then heated to 140°C again, kept at a constant temperature for 1 hour for staged temperature curing, and then cooled and demolded to obtain the resin material.
[0051] The resin materials prepared in Examples 2-6 and Comparative Example 1 were cut, and their tensile strength, tensile modulus, elongation at break, flexural strength and flexural modulus were tested, and photographed. Specific details are shown in Test Examples 1-3.
[0052] Test Example 1: Tensile strength, tensile modulus, elongation at break
[0053] Test samples: resin materials prepared in Examples 2-6 and Comparative Example 1;
[0054] A microcomputer-controlled electronic universal testing machine, model CMT4304, produced by MTS Industrial Systems (China) Co., Ltd., with a test speed of 5 mm / min, was used to test the tensile strength, tensile modulus and elongation at break in accordance with GB / T 1040.2-2006 standard.
[0055] The tensile strength is calculated according to formula (1):
[0056]
[0057] Where σ t is the tensile strength (MPa), P is the breaking load (N), b is the specimen width (mm), and h is the specimen thickness (mm).
[0058] The tensile modulus is calculated according to formula (2):
[0059]
[0060] Where Et is the tensile modulus (MPa), L0 is the measuring gauge length (mm), ΔP is the load increment of the initial straight line segment on the load-deformation curve (N), ΔL is the deformation increment L0 within the gauge length corresponding to the load increment ΔP (mm), b is the specimen width (mm), and h is the specimen thickness (mm).
[0061] The elongation at break is calculated according to formula (3):
[0062]
[0063] Where ε t is the elongation at break of the sample (%), ΔL b It is the elongation within the gauge length L0 when the specimen breaks (mm), and L0 is the measuring gauge length (mm).
[0064] Table 1 Summary of test results of tensile strength, tensile modulus and elongation at break
[0065] Serial number Tensile strength(MPa) Tensile modulus (MPa) Elongation at break (%) Example 2 57 2035 52 Example 3 56 1952 43 Example 4 55 1890 28 Example 5 57 2098 37 Example 6 59 2114 40 Comparative Example 1 57 2048 37
[0066] It can be seen from Table 1 that, compared with Comparative Example 1, Example 2-6 uses phenyltrimethoxysilane as the solvent of the catalyst, which eliminates the degassing step required when using dichloromethane, thereby improving the operating efficiency; the tensile strength and tensile modulus of Examples 2-6 are close to those of the Comparative Example, indicating that the phenyltrimethoxysilane that has been involved in the composition of the resin material has little effect on the overall resin material component; especially after comparing Example 2 and Comparative Example 1, it can be found that the elongation at break of the two samples is better in Example 2.
[0067] Test Example 2: Flexural Strength and Flexural Modulus
[0068] Test samples: resin materials prepared in Examples 2-6 and Comparative Example 1;
[0069] The bending strength and bending modulus tests were conducted using a microcomputer-controlled electronic universal testing machine (model CMT4304) from Meters Industrial Systems (China) Co., Ltd. at a test speed of 2 mm / min and in accordance with GB / T 9341-2008 standard.
[0070] The bending strength is calculated according to formula (4):
[0071]
[0072] Where σ t is the bending strength (MPa), p is the maximum load (N), L is the span (mm), b is the specimen width (mm), and h is the specimen thickness (mm).
[0073] The bending modulus is calculated according to formula (5):
[0074]
[0075] Where E t is the bending modulus (MPa), L is the span (mm), ΔP is the load increment corresponding to the initial straight line segment on the load-deflection curve (N), b is the specimen width (mm), h is the specimen thickness (mm), and ΔS is the mid-span deflection corresponding to the load increment ΔP (mm).
[0076] Table 2 Summary of flexural strength and flexural modulus test results
[0077] Serial number Bending strength(MPa) Flexural modulus (MPa) Example 2 86 1998 Example 3 83 1969 Example 4 79 1876 Example 5 93 2053 Example 6 95 2110 Comparative Example 1 85 2001
[0078] It can be seen from Table 2 that, compared with Comparative Example 1, Examples 2-6 use phenyltrimethoxysilane as the solvent of the catalyst, which eliminates the degassing step required when using dichloromethane, thereby improving operating efficiency; the flexural strength and flexural modulus of Examples 2-6 are close to those of the Comparative Example, indicating that the phenyltrimethoxysilane that has been involved in the composition of the resin material has little effect on the overall resin material component.
[0079] Test Example 3: Sample Appearance Photos
[0080] Test samples: resin materials prepared in Example 2 and Comparative Example 1;
[0081] Comparative Example 1 ( Figure 1 ) and Example 2 ( Figure 2 ) Use HUAWEI VOG-AL10 mobile phone for shooting, aperture value f / 1.6, exposure time 1 / 50s, ISO speed ISO-100, exposure compensation 0 steps, focal length 6mm, maximum aperture 1.35.
[0082] In addition, Figure 1 and Figure 2 As shown, the resin material obtained in Comparative Example 1 has a small amount of bubbles on the surface ( Figure 1 ), while the surface of the resin material product obtained in Example 2 is smooth and free of bubbles ( Figure 2 ), indicating that using phenyltrimethoxysilane instead of dichloromethane can improve the aesthetics of the parts.
[0083] Finally, it should be noted that the above is only a preferred embodiment of the present invention and does not limit it. Although this patent is described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions recorded in the aforementioned embodiments or to replace some of the technical features therein with equivalents. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention are included in the protection scope of the present invention.
Claims
1. A method for preparing a degassing-free thermosetting resin, characterized in that: The following steps are involved: A1. Fully mix 100 parts by mass of DCPD and 5 to 20 parts by mass of TCPD to prepare a uniform liquid; A2, dissolving 0.02-0.06 parts by weight of Grubbs second generation catalyst and 0.07-0.2 parts by weight of retarder in 5-10 ml of high boiling point silane coupling agent, and adding the mixture to the feed solution of step A1; A3. Inject the liquid material obtained in step A2 into the mold, heat it up in stages for curing, and demould to obtain the resin material.
2. The method according to claim 1, characterized in that: In step A2, the retarder is selected from one or any combination of triphenylphosphine, tributyl phosphite and tributyl phosphate.
3. The method according to claim 2, characterized in that The retarder is triphenylphosphine.
4. The method according to claim 1, characterized in that: In step A2, the high boiling point silane coupling agent is selected from at least one of phenyltrimethoxysilane, p-chlorophenyltrimethoxysilane, 3-aminopropyltriethoxysilane, mercaptopropyltrimethoxysilane, benzyltriethoxysilane, triethoxypentylsilane, methylcyclohexyldimethoxysilane and n-hexyltrimethoxysilane.
5. The method according to claim 4, characterized in that The high boiling point silane coupling agent is phenyltrimethoxysilane.
6. The preparation method according to claim 1, characterized in that: In step A2, the molecular structure of the Grubbs second-generation catalyst is:
7. The method according to claim 1, characterized in that In step A3, the staged curing conditions are: 0.25 to 1.5 hours at 60° C. and 0.5 to 1.5 hours at 140° C.
8. The method according to claim 7, characterized in that The staged curing conditions are: 0.25 hours at 60° C. and 1 hour at 140° C.
9. A PDCPD thermosetting resin prepared according to the method according to any one of claims 1 to 8.
10. The PDCPD thermosetting resin according to claim 9, characterized in that: The tensile strength of the resin is ≥55MPa, and the tensile modulus is ≥1890MPa.
11. The PDCPD thermosetting resin according to claim 9, characterized in that: The elongation at break of the resin is ≥28%.
12. The PDCPD thermosetting resin according to claim 9, characterized in that: The resin has a flexural strength of ≥79 MPa and a flexural modulus of ≥1876 MPa.